Theoretical and Experimental Study for Corrosion Inhibition of Carbon Steel in Salty and Acidic Media by A New Derivative of Imidazolidine 4-One - Al-Joborry, Nada Mohammed; Kubba, Rehab Majed (Iraqi Journal of Science, 2020)
A new imidazolidine 4-one derivative, of namly 2-[2-(4-Bromo-phenyl)-imidazo [1,2-a] pyridine-3-yl]-3-(4-nitro-phenyl)-imidazolidine-4-one (BPIPNP) was investigated as corrosion inhibitor for carbon steel in salty (3.5% NaCl) and acidic (0.5M HCl) solutions using potentiometric polarization measurements. The results revealed that the percentage inhibition efficiencies (%IE) in the salty solution (90.67%) are greater than that in the acidic solution (83.52%). Experimentally, the thermodynamic parameters obtained have supported a physical adsorption mechanism and which followed Langmuir adsorption isotherm. Density Functional Theory (DFT) of quantum mechanical method with B3LYP 6-311++G (2d, 2p) level was used to calculate geometrical structure, physical properties and inhibition efficiency parameters, in vacuum and two solvents (DMSO and H2O), all at the equilibrium geometry. The surface changes of carbon steel were studied using Scanning Electron Microscopy SEM and Atomic Force Microscopy (AFM) techniques.